Optimization of Pre-Treatment Condition of Luffa Cylindrica using Orthogonal Experiment - Teng, Yanhua; Lu, Man; Li, Hongyan; Wang, Xiyou; Xue, Changguo; Zhang, Mingxu (Asian Journal of Chemistry, 2014)
An optimization study on the pre-treatment of luffa cylindrica was described in this paper based on orthogonal experiments. The luffa fibers were treated by mixed treatment (sodium hydroxide and hydrogen peroxide). The effect of treatment on the structure of fibers was inspected by SEM and XRD. Based on the results of the range analysis, the maximum adsorbing yield was found at mixed solution of 20 % NaOH, 10 % H2O2 and reaction time 3 h. The SEM and XRD results revealed that the treatment wiped off lignin, pectin and hemicelluloses, more holes and grooves appeared on the surface and decreased the crystallinity index of treated fibers.